Plant derived bioactive compounds in human health and disease - book review - Nurma Arif, Noviani (Ethnobotany Research and Applications, 2025)
A review of Pathak S, Banerjee A. 2025. Plant derived bioactive compounds in human health and disease. CRC Press. doi: 10.1201/9781003486237. eBook ISBN9781003486237 “Plant Derived Bioactive Compound in Human Health and Disease,” edited by Surajit Pathak and Antara Banerjee, is a comprehensive exploration of the multifaceted roles of phytochemicals in promoting human health and combating diseases. Published in 2025 by CRC Press, this book serves as a vital resource for researchers, healthcare, professionals, and students interested in therapeutic potential of plant-derived compounds. The editors have curated a collection of chapters that delve into various aspects of phytochemicals, from their nutritional significance to their role in modern medicine.